PENGALAMAN IBU MENYUSUI DI MASA PANDEMI COVID-19 - Wulan Wijaya Wulan; Tetty Oktavia Limbong; Devi Yulianti; Fitra Amelia (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Background: The COVID-19 pandemic first occurred in China in December 2019 which has become a public health problem. WHO has declared Covid-19 a global pandemic. Almost all countries in the world are affected by Covid-19. Research objective: to review the experience of breastfeeding mothers during the Covid-19 pandemic. Method: This scoping review method consists of several steps, namely Identifying Scoping Review Questions, Identifying Relevant Literature Sources, Literature Selection, Compiling, summarizing, and reporting the results. Results: based on critical appraisal, 14 articles were obtained. The results found 3 themes, namely emotional burden, impact on breastfeeding practices, support and social needs. Conclusion: the experience of breastfeeding mothers during the Covid-19 pandemic can foster confidence and self-confidence for mothers to continue giving breast milk to their babies. The findings from this study can be used as a basis or input for future researchers to support breastfeeding practices and overcome challenges that arose during the COVID-19 pandemic